Knowledge, attitude and practice regarding hypertension among hypertensive patients in a teaching hospital in Selangor - Rajen Durai, Ruthpackiavathy; Mohd Zawawi, Muhammad Alif (Universiti Putra Malaysia, 2024)
Introduction: Hypertension, a significant health problem affecting around 1.28 billion persons aged 30 to 79 years and when not treated causes life-threatening complications which can damage vital organs leading to death. Knowledge, attitude, and practice (KAP) are important influential factors towards the treatment process of hypertension and lack of these may dangerously affect the health status of hypertensive patients. The main aim of this study was to determine the level of KAP regarding hypertension among hypertensive patients in an outpatient clinic in a teaching hospital, Selangor. Materials and methods: A cross-sectional study was carried out among 101 hypertensive patients using self-administered questionnaires. Data was analyzed by using the SPSS version 27.0 and presented in frequencies, percentages and Pearson chi-square. Results: This study found that the scores for the level of knowledge (good = 51.5%; fair = 25.7%; poor = 22.8%), attitude (good = 84.84%; fair = 8.9%; poor = 6.9%), and practice (good = 65.3%; fair = 26.7%; poor = 7.9%) among the participants were averagely high. In addition, there was an association between the level of knowledge and practice (p = 0.042) and attitude and practice (p = 0.000). Conclusion: Although the result showed positive outcomes, it is very important for healthcare personnel to continuously assess these levels as the prevalence of hypertension is still on the rise and the need arises to develop more appropriate educational and self-management programs to improve the health status and prevent complications among these patients.